The Effectiveness of Project Based Learning in Improving Student Learning Results and Motivation in Physical Education Learning - Mulya, Gumilar (Indonesian Journal of Sport Management, 2023)
In physical education learning, learning needs to be developed that motivates students to produce products through project-based activities. Project-based learning can be an alternative learning that teachers can carry out to increase students' understanding and motivation. This research aims to determine the effect of the project-based learning model on student learning motivation. This research uses a quantitative approach with the research design taken posttest control group design. This design was chosen to see the effectiveness of project-based learning in junior high school students. The population in this study were class VIII students at SMPN 6 Tasikmalaya City. This research was carried out for two months, namely February and March 2023, and was adjusted to the schedule of the two classes. Data collection techniques consist of the first type, and learning outcomes tests to measure student learning outcomes in football subjects, and questionnaires to see students' motivation in implementing learning. Data analysis was carried out univariate and bivariate. Based on the data analysis that has been carried out, project-based learning in physical education subjects helps students improve their abilities; apart from that, student motivation is better in project-based learning because there are the best products that must be produced.